2016
DOI: 10.1523/jneurosci.2847-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Slow Muscle Precursors Lay Down a Collagen XV Matrix Fingerprint to Guide Motor Axon Navigation

Abstract: The extracellular matrix (ECM) provides local positional information to guide motoneuron axons toward their muscle target. Collagen XV is a basement membrane component mainly expressed in skeletal muscle. We have identified two zebrafish paralogs of the human COL15A1 gene, col15a1aandcol15a1b,whichdisplaydistinctexpressionpatterns.Hereweshowthatcol15a1bisexpressedanddepositedinthemotorpathECM by slow muscle precursors also called adaxial cells. We further demonstrate that collagen XV-B deposition is both tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 49 publications
4
51
0
3
Order By: Relevance
“…Twenty potential genes were annotated according to these SNPs, and those specific trait-associated genes that we showed were paid more attention to. For example, there was a study that showed the loss of COL15A1 provoked muscle atrophy (Guillon et al, 2016). Another study showed that overexpression of RPL3L impaired the growth and myogenic fusion of myotubes (Chaillou, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty potential genes were annotated according to these SNPs, and those specific trait-associated genes that we showed were paid more attention to. For example, there was a study that showed the loss of COL15A1 provoked muscle atrophy (Guillon et al, 2016). Another study showed that overexpression of RPL3L impaired the growth and myogenic fusion of myotubes (Chaillou, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Its expression is associated with vascular, neuronal, mesenchymal and some epithelial basement membrane (BM) in many tissues, indicating a probable function in the adhesion between BM and the underlying connective tissue stroma . Its precise functions remain to be fully elucidated, even if evidence so far suggests that ColXV is involved in more sophisticated roles than just the molecular architecture of BM, particularly in the context of ECM organization and degradation .…”
Section: Introductionmentioning
confidence: 99%
“…Immuno-precipitations show that the C-type lectin domain of Chodl binds the collagenous domains of ColXIXa1 but does not bind ColXIIa1a. However, other collagens could also act as a ligand, such as ColXV, which possesses collagenous domains (Eklund et al, 2000) and for which the mutant phenotype is also similar to that of chodl mutants in zebrafish (Guillon et al, 2016). Cell transfection assays indicate that binding of extracellular ColXIXa1 by the extracellular C-type lectin domains of Chodl occurs at the plasma membrane.…”
Section: Colxixa1 Is a Binding Partner For Chodlmentioning
confidence: 99%
“…The horizontal myoseptum in zebrafish is rich in ECM factors, such as Tenascin-C (Schweitzer et al, 2005), Chondroitin sulfates (Zhang et al, 2004), and collagens (Guillon et al, 2016), which are likely to take part in synaptogenesis. The fact that ColXIXa1 is produced by muscle cells (Hilario et al, 2010) and Chodl by motor neurons (Zhong et al, 2012) makes it probable that these factors interact at the horizontal myoseptum synapses.…”
Section: Colxixa1 Is a Binding Partner For Chodlmentioning
confidence: 99%